Some notes about efficiency balanced block designs with repeated blocks - Ceranka, Bronisław (Metodološki zvezki, 2009)
Various problems for a class of efficiency balanced block designs based on balanced incomplete block designs with repeated blocks are considered.
Keywords: Matematična statistika; Mathematical statistics; statistične metode; raziskave